Experimental and numerical investigation for improving the thermal performance of a microencapsulated phase change material plasterboard. (15th October 2018) - Boudali Errebai, Farid; Chikh, Salah; Derradji, Lotfi
Highlights: Experimental measures of thermal properties of phase change material plasterboard. New method to improve heat absorption of phase change material plasterboard. Heat absorption and release can be increased by about 100% and 175% respectively. Proposal of an analytical model to compute the absorbed heat with a new technique. Abstract: The energy storage in buildings is a significant means for an optimal management of thermal energy. The use of phase change materials in a building envelope can improve heat storage capacity and the thermal behavior of the wall. However, the small thermal conductivity of the phase change materials slows down the process of heat absorption and release. The present study suggests a new technical solution for improvement of thermal behavior of a phase change material plasterboards. It consists of perforating the panel with several small holes yielding a greater contact surface area with the surrounding air. This passive enhancement technique is implemented experimentally and numerically to check its performance. Results show that the perforated panels produces an augmentation in heat absorption and release. The average increase was 100% for heat absorption and 175% for heat release as compared to a standard panel without holes. In addition, a perforated panel with a given thickness can absorb heat as much as a standard panel three to four times thicker. Furthermore, it was found that the absorbed and released heat flux values have a direct relationship with the ratio of the panel thickness to the holes spacing.